Hospitalitas Sebagai Upaya Mencegah Kekerasan dalam Memelihara Kerukunan dalam Relasi Islam - Kristen di Indonesia - Yohanes K. Susanta (Reformed Center for Religion and Society, 2015)
ABSTRACT:Â This paper shows that religious violence is a reality that characterizes the history of mankind. The inter-religious violence became a regular phenomenon that is often encountered in Indonesian society. Therefore, this paper will examine the causes of inter-religious violence in Indonesia, especially the relationship between Muslims and Christians. This paper will also show the task of the church in preventing inter-religious violence by promoting and applying hospitality. It does not mean that the church is the most responsible side for the violence, but the church is a part and become a witness of the history of violence that has occurred.Â KEYWORDS:Â hospitality, Christians-Muslims relationship, violence, religious harmony